Pemanfaatan Artificial Intelligence (AI) Sebagai Strategi Dakwah: Analisis peluang dan Tantangan - Batubara, Yenni (FDIK IAIN Padangsidimpuan, 2024)
In today's digital era, technology continues to develop rapidly and has a significant impact on various aspects of life, including in the field of Islamic preaching. One technology that is starting to get attention in the context of preaching is Artificial Intelligence (AI). The research method used is a literature study, with data sources of journal articles, papers, documents and websites. Then the data analysis technique used is descriptive analytical. The results of the study show that the use of AI as a preaching strategy offers various opportunities that can increase the effectiveness and efficiency in spreading Islamic teachings. However, there are challenges that must be overcome, especially related to ethics, technology dependence, accessibility, and acceptance of technology. Then with a wise strategy and approach and the development of the right framework, the use of AI in preaching can provide significant benefits without ignoring ethical and humanist values.